Design, implementation and evaluation of a mobile application to assess Goubak® game performance - Manso-Lorenzo, Víctor; Guijarro Jareño, Eva; González-Víllora, Sixto (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The use of mobile applications (apps) has spread in the practice of sports and has been transferred to the educational field, where the use of Information and Communication Technologies (ICT) is becoming more and more common. In this sense, it is the teacher’s responsibility to ensure the responsible use of ICT, which promotes learning. For this reason, this article presents a proposal for the teaching-learning of an alternative sport, Goubak®, through the use of an intuitive app in Physical Education. The proposal was implemented with 6th grade students in Primary School (10-12 years) in a public school in the Community of Madrid. The design of the app followed three phases (1) development of the app; (2) implementation of the thematic unit on Goubak® using the app in the classroom; (3) data collection. The Technology Acceptance Model (TAM) instrument was used to collect information, presenting a favorable Cronbach’s alpha (0.833), with a similar perception according to the sex. In addition, student and teacher perceptions were positive for the use of the Goubak® initiation app.